2019
DOI: 10.14475/kjhpc.2019.22.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Do Korean Medical Schools Provide Adequate End-of-Life Care Education? A Nationwide Survey of the Republic of Korea’s End-of-Life Care Curricula

Abstract: Purpose: Physician competency in end-of-life (EOL) care is becoming increasingly important. This study investigated the EOL care curricula in Korean medical schools. Methods: Questionnaires were issued to the faculty members responsible for the EOL care curricula at each of the medical schools. These included questions on the structure and content of the curricula, teaching methods, and faculty members' attitudes to the curricula. Results: Characteristics of the EOL care curricula were compiled from 27 (66%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…At the time this manuscript was being written, we were unable to find any other published curriculum assessment projects that used EFPPEC as a reference. There are several other published curriculum assessment studies that have referenced PEAT [9][10][11][12], but most of their aims and methods are quite dissimilar to our project. For example, Kim et al [9] assessed end of life care curricula by surveying directors or faculty members of 27 Korean medical schools, while Schiessl et al [10] reviewed 17 international UGME curricula identified by a literature search, with both studies reporting the proportion of their respective curricula that covered each PEAT objective and domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time this manuscript was being written, we were unable to find any other published curriculum assessment projects that used EFPPEC as a reference. There are several other published curriculum assessment studies that have referenced PEAT [9][10][11][12], but most of their aims and methods are quite dissimilar to our project. For example, Kim et al [9] assessed end of life care curricula by surveying directors or faculty members of 27 Korean medical schools, while Schiessl et al [10] reviewed 17 international UGME curricula identified by a literature search, with both studies reporting the proportion of their respective curricula that covered each PEAT objective and domain.…”
Section: Discussionmentioning
confidence: 99%
“…There are several other published curriculum assessment studies that have referenced PEAT [9][10][11][12], but most of their aims and methods are quite dissimilar to our project. For example, Kim et al [9] assessed end of life care curricula by surveying directors or faculty members of 27 Korean medical schools, while Schiessl et al [10] reviewed 17 international UGME curricula identified by a literature search, with both studies reporting the proportion of their respective curricula that covered each PEAT objective and domain. The different modes of data collection and output limit the utility of comparing results of our project to theirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most medical schools used lectures combined with small-group discussions, clinical clerkships, role play, or videos. 18 However, due to the Covid-19 situation, many lectures have been converted to online lectures, and active teaching methods have declined. In a recent study, many students had limited bedside experience and feedback from a clinical supervisor in end-of-life care (EOL) curricula; with students appearing to need more clinical experiences and feedback as these are paramount to the competencies of medical students.…”
Section: Editorialmentioning
confidence: 99%
“…There were 41 medical schools in Korea when the survey was conducted by Kim et al [14] in 2016. The authors of the study said the questionnaires were sent between March and May 2016. b) There were 40 medical schools in 2021.…”
mentioning
confidence: 99%